2-[(2,4-Dimethylphenyl)iminomethyl]-3,5-dimethoxyphenol - Tanak, Hasan (International Union of Crystallography, 2009)
X-ray analysis reveals that the title Schiff base compound, C(17)H(19)NO(3), possesses both OH and NH tautomeric character in its molecular structure. The occupancies of the enol and keto tautomers are 0.62 (3) and 0.38 (3), respectively. The presence of the minor keto form could not be confirmed from the IR spectrum. The molecule is approximately planar, the dihedral angle between the planes of the two aromatic rings being 6.97 (8)°. The molecular structure of the major component is stabilized by an intramolecular O—H⋯N hydrogen bond, which generates an S(6) ring motif (N—H⋯O hydrogen bond in the minor component).